2019
DOI: 10.22158/fet.v2n4p255
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Conflict Management Styles and Job Satisfaction of Private Islamic Secondary School Teachers

Abstract: Study aims to investigate about conflict management style and the job satisfaction among private Islamic school teachers. The data consisted of 136 samples from private secondary school teachers at Alor Setar district in Kedah. For acquiring the conflict management style, Rahim Organizational Conflict Inventory (ROCI-II) had been used and to gain the job satisfaction datum, the Teaching Satisfaction Scale (TSS) developed by Ho and Au in 2006 was used. The findings of this research revealed that style of compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…High levels of conflict can be associated with lower level of job satisfaction. For example, a correlation between conflict at work and the effectiveness of leaders and employees has been reflected on a negative correlation between conflict level and job satisfaction (Khun-inkeeree et al, 2019). For example, Chandolia & Anastasiou (2020) have reported that compared to the laissez-faire school leadership style, transformational leadership style was associated with low level of conflict at schools.…”
Section: Transformational Leadership and Conflict Managementmentioning
confidence: 99%
“…High levels of conflict can be associated with lower level of job satisfaction. For example, a correlation between conflict at work and the effectiveness of leaders and employees has been reflected on a negative correlation between conflict level and job satisfaction (Khun-inkeeree et al, 2019). For example, Chandolia & Anastasiou (2020) have reported that compared to the laissez-faire school leadership style, transformational leadership style was associated with low level of conflict at schools.…”
Section: Transformational Leadership and Conflict Managementmentioning
confidence: 99%
“…As for management studies, only 9% of studies typically examined quality and accountability processes (Abdul Khalil and Awang, 2016;Ismail and Don, 2015), discipline management (Ghani et al, 2014), curriculum management (Awang Besar and Hj Ahmad, 2013;Mohd Hamzah and Ayob, 2015), safety management (Naranasamy and Adams, 2019;Ramachandran and Kenayathulla, 2018), conflict management (Khun-inkeeree et al, 2019), financial management (Mohd Arus et al, 2018), and human resource management (Hj Ahmad, 2009). The distribution of the Malaysian EDLM studies corroborates with the global literature in EDLM, which has demonstrated a preference on studying leadership in recent years (Mertkan et al, 2016).…”
Section: Leadership and Managementmentioning
confidence: 99%